Craniofacial and Upper Airway Development in Patients With Treacher Collins Syndrome. Issue 7 (October 2021) - Lin, Yanxian; Ma, Xiaoyang; Huang, Yuanliang; Mu, Lin; Yang, Liya; Zhao, Minghao; Xie, Fang; Zhang, Chao; Xu, Jiajie; Lu, Jianjian; Teng, Li
Abstract : Abstract: This study evaluated age-associated morphology changes in the cranial base, facial development, and upper airway of patients with Treacher Collins syndrome (TCS). A total of 33 preoperative computed tomographic images (TCS, n = 14; control, n = 19) were included in the study and divided into three age-related subgroups (2–6 years, 7–18 years, and older than 18 years). Linear, angular cephalometric measurements and upper airway volumes were collected. All measurements were analyzed using ProPlan CMF software (version 3.0; Materialize, Leuven, Belgium). The association between aging and upper airway morphology was analyzed. Compared to control subjects, TCS patients had a smaller cranial base, maxilla, and nose; they also had reduced upper airway volume compared to control subjects. The observed differences were most significant in patients between the ages of 7 and 18 years. This study used computed tomography-based three-dimensional analyses to provide a detailed description of age-related changes that occur in craniofacial measurements and upper airway volumes in children, adolescents, and young adult patients with TCS in China. These data can be used to evaluate individual patients with TCS and to select treatment to improve the growth of the craniofacial region. Abstract : Supplemental Digital Content is available in the text